Oragnizational forms in Icelandic firms in volatile business environment 2007-2016 - Óladóttir, Ásta Dís; Óskarsson, Guðmundur Kristján; Eðvarðsson, Ingi Rúnar (Research in applied business and economics, 2016)
The aim of this article is to compare the organisational structure (organisational charts) of Icelandic companies in the period 2007-2016. Surveys by the authors from 2007 and 2016 are compared and an analysis carried out of whether economic fluctations affected the companies’ organisational structure. The article is based on the results of an online survey administered by the University of Akureyri Research Centre in 2007 and the Faculty of Business Administration at the University of Iceland in 2016. The managers of 222 companies responded to the survey in 2007 and 120 companies responded to the survey in 2016 and the response rate was 46,15% in 2007 and 24,4% in 2016. The comparison of the surveys indicate that economic fluctations do not have much influence on the organisational structure of the companies that participated in the research. However, it needs to be mentioned that 36.4% of the firms did merge with other firms, did take over other companies or made other organisational changes after the financial crisis in 2008. The companies have more employees after the collapse, their managers are more educated, and more women are in positions of power than (there were) prior to the collapse. The size of the companies influences various aspects of their organisation. Larger companies are more formal and have more specialisation and a defined organisational structure, have three or more management levels and are more likely to be organised in accordance to a matrix structure. Also, it is revealed that a more stable operational environment increases the probability that functional structure is in place. Markmið þessarar greinar er að skoða hvort efnahagssveiflur hafi áhrif á skipulagsform (skipurit) íslenskra fyrirtækja. Bornar eru saman kannanir höfunda frá árinu 2007 og árið 2016 og greint hvort efnahagssveiflur hafi haft áhrif á skipulagsform viðkomandi fyritækja. Spurt var í síðari könnuninni hvort einhverjar skipulagsbreytingar hefðu orðið á undanförnum fimm árum, eða til ársins 2011, áður en uppsveifla ...